Penerapan Metode First-In First-Out (FIFO) Komputerisasi Persediaan Barang pada Pergudangan untuk Mengoptimalkan Perputaran Persediaan - Hafizh Subagja; Tegar Rihanjaya; Fauzi Nur Afansyah; Abdul Rahman; Yudi Prasetyo (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the implementation of the First-In First-Out (FIFO) method in a computerized inventory management system for warehousing to optimize inventory turnover. The system was developed using a structured software architecture represented through class diagrams and sequence diagrams to ensure clear data relationships and well-defined process flows. The application integrates hardware and software specifications that support stable data processing, accurate transaction recording, and reliable reporting. The FIFO method ensures that goods entering the warehouse earlier are prioritized for release, reducing the risk of stock accumulation and improving inventory control efficiency. The results indicate that the computerized FIFO-based inventory system enhances operational effectiveness, improves stock accuracy, and supports compliance with accounting standards related to inventory valuation. Furthermore, the system provides timely and reliable inventory information that assists management in decision-making processes. The implementation of a FIFO-based computerized inventory system is proven to be an effective solution for improving warehouse inventory management performance and supporting sustainable operational efficiency.